Commentary on Part 3: International political and economic structures - Farrelly, Colin (Les ateliers de l'éthique / The Ethics Forum, 2013)
Mathias Risse’s On Global Justice is a unique and important contribution to the growing literature on global justice. Risse’s approach to a variety of topics, ranging from domestic justice and common ownership of the earth, to immigration, human rights, climate change, and labour rights, is one that conceives of global justice as a philosophical problem. In this commentary I focus on a number of reservations I have about approaching global justice as a philosophical rather than an inherently practical problem. To his credit Risse does acknowledge at various stages of the book that a good deal of the applied terrain he ventures into presupposes complex and contentious empirical assumptions. A greater emphasis on those points would, I believe, helpfully reveal the shortcomings of tackling intellectual property rights by appealing to Hugo Grotius’s stance on the ownership of seas, or the shortcomings of tackling health by invoking the language of human rights without acknowledging and addressing the constraints and challenges of promoting health in an aging world.